Progress in TLR4/NF-κB Pathway Regulation by Traditional Chinese Medicine for the Treatment of Polycystic Ovary Syndrome - Li, Yue; Zhu, Hongli (Journal of Contemporary Medical Practice, 2024)
Polycystic ovary syndrome (PCOS) is a common reproductive endocrine disease in women, affecting women's fertility and cardiovascular system. Due to the complexity of its pathogenesis, there are many adverse reactions commonly used in clinical treatment, and the therapeutic effect is short-lived and temporary. TLR4/NF-κB pathway is a classical signaling pathway related to inflammation, and the effective components of TCM compounds and TCM monomers have been proven to reduce the levels of various inflammatory factors in patients by regulating the TLR4/NF-κB pathway, so as to achieve the effect of PCOS. The potential value of TCM in prevention and treatment of PCOS based on TLR4/NF-κB pathway was revealed. This article aims to summarize the recent studies on the improvement of PCOS symptoms by regulating the expression of TLR4/NF-κB pathway by Chinese medicine, so as to further study the mechanism of PCOS prevention and treatment by this pathway under the regulation of Chinese medicine, so as to open up new ideas for the development of new drugs targeting this pathway and clinical research.